Controle litoestrutural nos relevos graníticos sobre o batólito de Quixadá e Entorno-CE - Castro, Henrique Sampaio de (2018)
This research proposes to interpret the geomorphological evolution of the inselbergs field of Quixadá and surroundings. The study area is located in the state of Ceará, in the geotherctonic province of Borborema, in the area of Central Ceará. The studies were conducted by Structural Geomorphology, showing that the structure of structures generated in rocks, as a result of the granitoid intrusion (magmatic housing process), added to the structures generated in moments of ductile kinematics (shear zones, metamorphic foliation, mineral and micro-granular enclaves) and structures generated in rheumatic kinematics (faults, joints and diaclases), condition the greater susceptibility to rock weathering. This translates into the landscape as the contrast of topographical ups and downs (Inselbergs, nubbins, buornhartds, massifs and plains) and in geomorphological features such as: fluting, dissolving basins, taffones and kettles and Honeycombs and boulders. The arguments that prove these statements are the result of fieldwork supported by SRTM images, with a pixel of thirty meters, used to contextualize the reliefs regionally. High resolution aerial imagery made by drone in four outcrops (one pair of inselbergs and one pair of nubbins), aerial survey data generated digital elevation models (MDE), with a pixel of about 8 centimeters, orthophotomosaic pixel close to 2 centimeters) and topographic model in three dimensions.